Expressions of pl6ink4a, p27kipl and p21 waf1 in differentiating primary adenocarcinoma of endocervix from endometrium - Farveen Marican, Abu Backer Maricar (2010)
The distinction between an endocervical adenocarcinoma (ECA) and an endometrial adenocarcinoma (EMA) can be problematic on small biopsies or when there is tumor in both endocervical and endometrial specimens or when the tumor has extended into the lower uterine segment. The judgment is difficult to be based on histomorphology alone because these tumors can have similar histologic appearance. We investigated the value of pl6INK4a, p21WAFl and p27kipl immunohistochemistry for distinguishing ECA and an EMA. We immunostained tissue sections of archival samples from 2005 to 2008 from HUSM and HSB. The immunohistochemical staining scores were correlated with their clinicopathologic parameters. There were 40 ECA and 92 EMA cases examined. We observed significant higher expressions of pl6INK4a and p27kipl ([p <0.001] (80% versus 25%) and [p=0.001] (43% versus 15%)) in ECA than in EMA. ECA could be differentiated from EMA based on the combination expressions of pl6INK4a and p 27kipl. p21WAFl expression did not differentiate these two carcinomas (70% versus 78%, p=0.312). There was significant association seen between negative pl6INK4a expression and low histologic grade in EMA (p=0.014). In ECA, p21WAFl expression shows significant association with corpus infiltration (p-0.043) while negative p27kipl expression with lymph node invasion (p=0.030). Multivariate analysis however shows no association between lymph node invasion and p27kipl expression adjusted by race, histologic grade, vascular invasion, p21WAF1 expression and extension into the uterine corpus. In conclusions, combination of p!6INK4a and p27kipl expression is helpful in differentiating ECA from EMA. In small biopsy, the expression of p21WAFl may help in assessing the presence of corpus infiltration. P27kipl expression is helpful in predicting presence of lymph node invasion.